Determination of shear support capacity of transfer beam with varied section - Il-Ju Ri; Song-Hyon Han (Talenta Publisher, 2021)
In the RC structure with transfer beam, if the beam is fixed with the column under the transfer layer, it will cause very big reaction of the support at the supporting point and can cause the serious breaking because the section of the transfer beam is very big. It’s not easy to make the section big for the whole length, so I studied about how to applicate the transfer beam with varied section to increase the capacity by changing the section of the beam around the supporting point. In this thesis, I suggested the formulars of the shear capacity of transfer beam with varied section by using the program ABAQUS.